Pengaruh Stabilitas Finansial, Literasi Keuangan dan Fear of Missing Out (Fomo) terhadap Keputusan Investasi Pasar Modal di Kalangan Mahasiswa Fakultas Ekonomi dan Bisnis Unsoed - Putra, Mochammad Razan Yuwono; Fauzi, Pahrul (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This research was conducted at Jenderal Soedirman University with the aim of analyzing: (1) the effect of financial stability on the investment decisions of FEB students, (2) the effect of financial literacy on the investment decisions of FEB students, and (3) the effect of FoMO (Fear of Missing Out) on the investment decisions of FEB students. The study involved 135 FEB students at Unsoed who actively invest in the capital market. Primary data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that: (1) financial stability has no significant effect on students’ investment decisions, (2) financial literacy has a positive and significant effect on investment decisions, and (3) FoMO also has a positive and significant effect on investment decisions. Collectively, the three variables influence investment decisions, with a coefficient of determination (R²) of 56.9%.